Kajian Penaikan pH dan Oksidasi Ozon terhadap Konsentrasi Phospat dan Deterjen dalam Air Limbah di Laboratorium Kesehatan Daerah Kabupaten Semarang - Suhirman Suhirman; Nur Endah; Sulistyani Sulistyani; Muhammad Nur (Youngster Physics Journal, 2018)
One of human activity is health Laboratory which is it activity would produce waste water that can environment contaminate . Some of  substance that consisted in laboratory waste water are, phospat dan deterjent which is  contain Linear alkylbenzene sulfonate (LAS). These parameter should to be processed before lost upon to environment or river. The choice to ozone technology consideratly that this technology is good technology (no side effect), Cheap relativly, no wide area needed and more practically. The ozone tecnology that be chosen is Advance Oxidation Processes (AOP)  with altering pH waste water to pH 9. In this manner we hope produce more OH radical that have more higher potential oxidation than ozone elone. The aim of this research is: to study altering pH and ozone oxidation concerning consentration of phospat and deterjent waste water of Health Laboratory at Semarang regency. Research type was True eksperimen with desain Posttest-Only Control Design, laboratory scale.The yields after oxidation proces with ozone  was : rate value of phospat concentration was 3,62 ppm at 10 minutes, 3,45 ppm at 20 minutes, 3,35 ppm at 30 minutes and 3,28 ppm at 45 minutes.Rate value of LAS concentration was 0,21 ppm at 10 minutes, 0,17 ppm at 20 minutes, 0,14 ppm at 30 minutes and 0,17 ppm at 45 minutes..Analysis yield : there was not difference  about phospat consentration on pH altering and ozone oxidation (Sig. 0,965 > 0,05), there was not difference  about LAS consentration on pH altering and ozone oxidation  (Sig. 0,7890 > 0,05). Keyword : Advance Oxidation Proceses, Ammonia, Phospat, Linear alkyl Benzenesulfonat